Board depicting the name 'Club of St Anthony (Deussua)' - Mumbai Archive Project (Jio Institute, 2024)
The Club of St. Anthony is located close to Dockyard railway station on the Harbour Line, making it a convenient place to stay for those travelling by train. Kudds are associated with their place of origin, typically a Goan village which provides patronage and members to the club. The Club of St. Anthony was established for visitors from Deussua village, Chinchinim.